2002
DOI: 10.4319/lo.2002.47.2.0515
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Fe and Cu on growth and domoic acid production by Pseudo-nitzschiamultiseries and Pseudo‐nitzschia australis

Abstract: Toxigenic pennate diatoms of the genus Pseudo-nitzschia produce domoic acid (DA), the neurotoxin linked to amnesic shellfish poisoning. We investigated how Fe and Cu affect growth and DA production by P. multiseries and P. australis clones isolated from Monterey Bay, California. Growth rates of these species could be inhibited by both Fe limitation (pFe 20.5, ϭ 50% max ) and Cu toxicity (pCu 10.5, ϭ 30-50% max ). The rate of DA production during the exponential phase was a significant inverse function of cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
213
2
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(229 citation statements)
references
References 56 publications
11
213
2
3
Order By: Relevance
“…Maldonado et al (2002) found that P. multiseries and P. australis produced DA during the exponential growth phase in iron-deficient or toxic copper concentrations. Almost all (95%) of the DA produced was released into the medium and the authors concluded this to be a stress reaction against unfavorable micronutrient levels (Maldonado et al, 2002). In the present study, ∼60% of the total DA produced (cellular and dissolved) by P. seriata in physical contact with C. hyperboreus was released into the medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maldonado et al (2002) found that P. multiseries and P. australis produced DA during the exponential growth phase in iron-deficient or toxic copper concentrations. Almost all (95%) of the DA produced was released into the medium and the authors concluded this to be a stress reaction against unfavorable micronutrient levels (Maldonado et al, 2002). In the present study, ∼60% of the total DA produced (cellular and dissolved) by P. seriata in physical contact with C. hyperboreus was released into the medium.…”
Section: Discussionmentioning
confidence: 99%
“…nutrients in relation to the growth phase (reviewed in Bates, 1998;Lelong et al, 2012), pH (e.g. Lundholm et al, 2004), and trace metal limitation or toxicity (Maldonado et al, 2002). Evidence of allelopathic effects of DA, however, has not been found (Lundholm et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both OA and temperature can affect biological growth and generation of organic ligands, potentially favouring growth of specific phytoplankton species and inducing a shift in the community structure unrelated to Fe (e.g., Tortell et al, 2008a;Trimborn et al, 2014). As different biological communities excrete different iron-binding ligands (Trick and Wilhelm, 1995;Maldonado et al, 2002;Hassler et al, 2015;Norman et al, 2015), a shift in community structure or changes in Fe-stress could have a greater impact on Fe chemistry and bioavailability than those associated with changes in temperature and pH (Gledhill et al, 2015). However, the effect that the modulation of the excretion of organic ligands associated with basal biological activity or the change in the nature of organic ligands associated with a shift in community will have on Fe chemistry and bioavailability is yet to be investigated.…”
Section: Iron (Fe) Limitationmentioning
confidence: 99%
“…Although Pseudonitzschia cells can release relatively large amounts of DA in the water column, especially under macronutrient- (Bates, 1998)o r iron-limitation (Maldonado et al, 2002), only minor toxin incorporation (0.3-0.6% of available DA in 5-24 h) has been reported from the dissolved phase by mussels Novaczek et al, 1991). Fast photodegradation (Bouillon et al, 2006) may further limit the availability of dissolved DA to marine organisms.…”
Section: Introductionmentioning
confidence: 99%